2016
DOI: 10.3389/fnbeh.2016.00072
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Evolutionary Patterns of Functional Connectivity in Sensorimotor and Cognitive Regions after Stroke

Abstract: The human brain is a highly connected and integrated system. Local stroke lesions can evoke reorganization in multiple functional networks. However, the temporally-evolving patterns in different functional networks after stroke remain unclear. Here, we aimed to investigate the dynamic evolutionary patterns of functional connectivity density (FCD) and strength (FCS) of the brain after subcortical stroke involving in the motor pathways. Eight male patients with left subcortical infarctions were longitudinally ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Actually, patterns of FC changes in cognitive areas presented in our work were consistent with previous longitudinal studies. Enhanced FC alterations associated with cognitive function could appear immediately after stroke onset and remain at high levels for weeks or months, even in patients with recovered motor function ( 8 , 36 ). These changes may indicate a neural mechanism of long-term cognitive compensation for motor dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, patterns of FC changes in cognitive areas presented in our work were consistent with previous longitudinal studies. Enhanced FC alterations associated with cognitive function could appear immediately after stroke onset and remain at high levels for weeks or months, even in patients with recovered motor function ( 8 , 36 ). These changes may indicate a neural mechanism of long-term cognitive compensation for motor dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a growing number of studies are employing this technique to map the spatio‐temporal covariance structure of networks of spontaneous brain activity to investigate the reorganization of motor function following stroke (Golestani, Tymchuk, Demchuk, Goodyear, & Group, ; Wang et al, ; Yin et al, ). Many resting‐state studies have accordingly shown the altered functional connectivity of both sensorimotor and higher order cognitive control regions (Liu, Tian, Qin, Li, & Yu, ; Park et al, ; Zhao et al, ). In addition, many previous studies that described tasks and seed‐based FC engaged more than basic sensorimotor processes, such as the abnormal activation or FC in temporal and occipital regions (Park et al, ; Ward et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In literature, decreased interhemispheric functional connectivity is described in rats and humans after stroke to be associated with impaired sensorimotor function [ 6 , 47 , 50 , 52 ], and our study adds to this concept for the domain of arm and hand somatosensory deficits. Carter et al [ 48 ] presented an association between a disruption in interhemispheric functional connectivity of the sensorimotor network and upper extremity motor impairments in the acute phase post stroke.…”
Section: Discussionmentioning
confidence: 62%
“…Our results extend these prior findings by showing that already at one week after stroke, the extent of altered (reduced) inter-hemispheric functional connectivity of the somatosensory network is associated with more severe impairments in somatosensory function. Together, these observations highlight the behavioural relevance of the integrity of resting-state inter-hemispheric connectivity for both motor and somatosensory function and therefore provide further support to the notion that assessments of restorations/normalizations of these altered interhemispheric connectivity patterns may form a reliable index for evaluating the effectiveness of rehabilitation therapies at the neural level [ 6 , 17 , 52 ].…”
Section: Discussionmentioning
confidence: 68%